Stigma during COVID-19 pandemic among healthcare workers in greater Jakarta metropolitan area: a cross-sectional online study - Ika Saptarini; Novianti Novianti; Anissa Rizkianti; Iram Barida Maisya; Suparmi Suparmi; Ginoga Veridona; Ning Sulistiyowati; Sudikno Sudikno (Sekretariat Badan Penelitian dan Pengembangan Kesehatan, 2021)
Background: COVID-19, which started in Wuhan, has become a global pandemic leading to a new global risk to human health. Lack of information or misinformation about COVID-19 can lead to stigmatization, including for health workers. This study aims to determine the stigmatization among health workers during the COVID-19 pandemic within the Greater Jakarta Metropolitan Area. Methods: This study was a cross-sectional study conducted online using Google Forms in the Jabodetabek area. The questionnaire’s link was distributed through social media, including Whatsapp, Facebook, Twitter, and Instagram. The study sample is health workers who live in Jabodetabek and carry out health practices. Stigma is measured using four dimensions: personalized stigma, disclosure concerns, public attitudes, and negative self-image. Result: The negative self-image dimension is the dimension most felt by health workers. More than half of health workers agreed that during the COVID-19 pandemic, they put their families at risk because of their status as health workers. The stigma of health workers who work in hospitals is higher than that of non-hospital health workers, such as health centers, clinics, and laboratories. Conclusion: There was any stigmatization among healthcare workers in Greater Jakarta Metropolitan Area. Stigmatization was higher among healthcare workers who work in hospitals compared to those who work in non-hospitals. Some efforts should be made to reduce stigmatization among health workers, such as provide correct information to the public, equip health personnel with adequate personal protective equipment, and give incentives periodically to the health workers. Keywords: Stigma, COVID-19, healthcare workers, Greater Jakarta Metropolitan Area Abstrak Latar belakang: COVID-19 yang bermula dari Wuhan telah menjadi pandemi global yang mengancam kesehatan umat manusia. Kurangnya informasi atau informasi yang salah mengenai COVID-19 dapat menyebabkan adanya stigmatisasi termasuk terhadap tenaga kesehatan. Penelitian ini menilai adanya stigmatisasi terhadap tenaga kesehatan selama pandemi COVID-19 di wilayah Jabodetabek. Metode: Penelitian ini merupakan penelitian potong lintang dan dilakukan secara daring menggunakan Google Form di wilayah Jabodetabek. Tautan pengisian kuesioner disebarkan melalui media sosial seperti Whatsapp, Facebook, Twitter dan Instagram. Sampel studi adalah tenaga kesehatan yang tinggal di Jabodetabek dan melakukan praktik kesehatan. Stigma diukur menggunakan empat dimensi yaitu personized stigma, disclosure concerns, concerns about public attitudes dan negative self-image. Hasil: Dimensi negative self-image merupakan dimensi yang paling dirasakan oleh tenaga kesehatan. Lebih dari separuh tenaga kesehatan setuju bahwa selama pandemi COVID-19 mereka membahayakan keluarga mereka karena status mereka sebagai tenaga kesehatan. Stigma pada tenaga kesehatan yang bekerja di rumah sakit lebih tinggi disbanding tenaga kesehatan yang bekerja bukan di rumah sakit seperti puskesmas, klinik dan laboratorium. Kesimpulan: Terdapat stigmatisasi pada petugas kesehatan di jabodetabek. Stigmatisasi lebih tinggi di antara petugas kesehatan yang bekerja di rumah sakit dibandingkan dengan mereka yang bekerja tidak di rumah sakit. Beberapa upaya yang perlu dilakukan untuk mengurangi stigmatisasi di kalangan petugas kesehatan, seperti memberikan informasi yang benar kepada masyarakat, melengkapi tenaga kesehatan dengan alat pelindung diri yang memadai, dan memberikan insentif kepada mereka secara berkala. Kata Kunci: Stigma, COVID-19, tenaga kesehatan, jabodetabek